Study of the dynamic performance of a gabion wall. (April 2023) - Mummadisingh, Jyothi Visali; Sengupta, Aniruddha
Highlights: Frequency has a significant effect on acceleration and displacement responses. Provision of embedment to the gabion wall reduces responses. Damping of wall obtained from tests increases with an increase in base acceleration. Inclusion of damping in the numerical model yields better match with experiments. The numerical model is validated against a large size gabion wall with backfill. Abstract: Due to the wide increase in the usage of gabion-faced retaining walls in seismically active zones, like the Himalayas in India, it has become necessary to analyze the performances of gabion structures under dynamic conditions. In this study, in the absence of any full-scale dynamic test, shake table tests are conducted on a scaled-down (1:6.7) model gabion wall (without backfill) for different base accelerations (0.1 g, 0.2 g, 0.3 g, and 0.4 g) and frequencies (3 Hz, 5 Hz, 7 Hz, and 9 Hz). The performance of the gabion wall with and without bottom embedment is analyzed in terms of percentage displacements and acceleration amplification factors at different elevations. It is observed that the percentage displacements and acceleration amplification factors increase significantly with the increase in the frequency of the base motion. The bottom embedment has reduced the acceleration amplification factor at the top of the wall by a maximum of 8 %. The maximum lateral deformations are 0.9 % and 1 % of the height of the wall, with and without embedment, respectively. No damage to the gabion mesh, and no sliding at the base of the wall, is observed even at higher accelerations and frequencies. A finite element analysis, has been carried out to numerically simulate the observed behavior of the gabion wall in the shake table tests. The natural frequency and the damping of the gabion wall are calculated from the experimental free vibration responses and are utilized to derive Rayleigh damping coefficients. The inclusion of damping and the adoption of appropriate interaction properties between the gabion basket and the gravel fill/sand determined from the shake table tests have helped in achieving a good agreement between the numerical results and the experimental data. A large-scale shake table test on a gabion wall with backfill reported by Nakasawa et al. has been numerically simulated using the developed numerical model. A good match between the large scale experiment and the numerical results shows the validity and efficacy of the proposed model.